2015
DOI: 10.1097/ncc.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship Between Hopelessness Levels and Coping Strategies Among the Family Caregivers of Patients With Cancer

Abstract: This study could be used to help develop nursing interventions and efficient coping strategies. It suggests how oncology nurses may support family caregivers to increase their level of hope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…The same is true for hope. While hope has been shown in the literature to be a protective factor , it is not possible to rule out that caregivers who perceive only limited burden feel more hope than caregivers who are overwhelmed by their caring tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for hope. While hope has been shown in the literature to be a protective factor , it is not possible to rule out that caregivers who perceive only limited burden feel more hope than caregivers who are overwhelmed by their caring tasks.…”
Section: Discussionmentioning
confidence: 99%
“…These emotional complications can decrease quality of life and impede the ability for personal growth that allows a person to move in a positive life direction (Birkeland, Skogbrott, & Blix, 2015). Tokem, Ozcelik, and Cicik (2014) found a negative correlation between increased hopelessness and problem-focused coping strategies (optimistic approach and seeking social support; r = −.484, p < .01; r = −.190, p < .05, respectively). Jakupcak et al (2011) found that unrelieved feelings of hopelessness dramatically increased symptoms of psychological stress, including suicidal ideation, in a group of veterans with diagnosed posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 93%
“…Diagnosis and treatment of cancer in children caused some unique challenges for children and their families. Children with cancer's family members and their caregivers experience immense psychological distress, financial and relationship problems, and low quality of life so they need support, information, and advice (1,2).…”
Section: Introductionmentioning
confidence: 99%